Reaction time trends in the sprint and hurdle events at the 2004 Olympic Games: Differences between male and female athletes - Babic, V.; Delalija, A. (New Studies in Athletics, 2009)
Reaction time values, though very small, can differentiate overall performance in sprint races, where the margin of victory is often measured in thousandths of a second. This study, the second from a project examining the sprint and hurdle events at the 2004 Olympia Games in Athens, aimed to determine the differences in reaction times between male and female athletes. The results confirm previous findings that mean reaction time values are less for men than for women. However, unlike with the women, statistically significant differences for different competitive levels (defined by how far the athlete advanced in the competition) within the analysed events were not found for the men and, therefore, it was not possible to use reaction time as a parameter for drawing conclusions about competitive quality, It was found that men had significantly better mean reaction time values at all levels in three events: 100m, 110m hurdles and 400m hurdles. Interestingly, men had better reaction times only at the lower competitive levels of some events (first and second rounds) while the men and women finalists in most events did not differ significantly in reaction time. In the 200m men and women did not differ in reaction time at any level.